Aktivitas Antibakteri Isolat Bakteri Endofit dari Tanaman Miana (Coleus scutellariodes [L.] Benth.) terhadap Staphylococcus aureus dan Escherichia coli - Dwi Endah Kusumawati; Fachriyan Hasmi Pasaribu; Maria Bintang (IPB University, 2014)
Coleus scutellarioides [L.] Benth. known as medicinal plant which contains antidiarhea and antimicrobial compounds. Extraction of bioactive compound from plants is not efficient because it needs a large biomass, therefore the one of appropiate ways is using endophytic bacteria. The purpose of this research was to isolate and test of antibacterial activity of endophytic bacteria from Coleus scutellarioides [L.] Benth. against two pathogenic bacteria i.e Eschericia coli and Staphylococcus aureus. A total of 22 isolates of endophytic bacteria were obtained from Coleus scutellarioides [L.] Benth. Based on antibacterial activity test, 13 isolates of endophytic bacteria were able to inhibit the growth of E. coli and 15 isolates were able to inhibit S. aureus, whereas endophytic bacteria which can inhibit both types of pathogens are 10 isolates.